Elaboración de materiales compuestos AlN/AZ91E con preformas hechas por medio de colada en gel - Martínez Molina, Rodrigo Alan (Universidad Michoacana de San Nicolás de Hidalgo, 2018)
In this work, a metal matrix composite material was manufactured using the AZ91E magnesium alloy as a matrix. For this purpose, the process of manufacturing an interconnected porous sponge of aluminum nitride with powders of 8 μm in average particle size was developed by gelcasting with the polymerization of acrylamide and methacrylamide as gel formers. The tests by infrared spectroscopy determined that the polymers obtained were polyacrylamide (PAM) and polymethacrylamide (PMA). By means of differential scanning calorimetry the pyrolysis temperature of the gels was determined, of 207 ° C and 231 ° C, for polyacrylamide and polymetracrilamide, respectively. The gel was sintered and eliminated at a temperature of 1400 ° C for 1 h in an inert argon atmosphere reaching porosities of up to 85% by volume with a pore size ranging from 10 μm to 1000 μm. Subsequently, the foams were infiltrated with the alloy at 900 ° C for 30 min in an argon atmosphere. The x-ray diffraction technique was used to characterize the phases present in the foams and in the composite materials manufactured, where the presence of residual alumina was found after the pyrolysis of the gel, it was characterized microstructurally by performing elementary mappings by scanning electron microscopy , the hardness of the composite materials obtained was measured giving averages of 225 HV for those made with PMA and 176 HV for those made with PAM. The thermal conductivities of the composite materials were 50 W/(m*K) and 65 W/(m*K) for those composite made with PAM and PMA, respectively.

En este trabajo, se fabricó un material compuesto de matriz metálica empleando como matriz la aleación de magnesio AZ91E. En principio, se desarrolló el proceso de manufactura de una esponja porosa interconectada de nitruro de aluminio con polvos de 8 μm de tamaño promedio mediante colada en gel acuosa con la polimerización de acrilamida y metacrilamida como formadores de gel. Las pruebas por espectroscopía de infrarrojo determinaron que los polímeros obtenidos fueron poliacrilamida (PAM) y polimetacrilamida (PMA). Por medio de calorimetría diferencial de barrido se determinó la temperatura de pirólisis de los geles, de 207 °C y 231 °C, para la poliacrilamida y la polimetracrilamida respectivamente. Se sinterizó y eliminó el gel formado a una temperatura de 1400 °C durante 1 h en atmósfera inerte de argón alcanzando porosidades de hasta un 85% en volumen con un tamaño de poro que va desde 10 μm hasta 1000 μm. Posteriormente las espumas fueron infiltradas con la aleación a 900 °C durante 30 min en una atmósfera de argón. Se utilizó la técnica de difracción de rayox X para caracterizar las fases presentes en las espumas y en los materiales compuestos fabricados, donde se encontró la presencia de alúmina residual después de la pirolisis del gel, se caracterizó microestructuralmente realizando mapeos elementales mediante microscopia electrónica de barrido, se midió la dureza de los materiales compuestos obtenidos dando promedios de 225 HV con los hechos de PMA y 176 HV con los hechos de PAM. La conductividad térmica de los materiales compuestos fue de 50 W/(m*K) para los hechos de PAM y 65 W/(m*K) para los de PMA.
Instituto de Investigación en Metalurgia y Materiales. Maestría en Metalurgia y Ciencias de los Materiales
Keywords: info:eu-repo/classification/cti/7; IIMM-M-2018-0124; Magnesio; Esponjas; Nitruro de aluminio; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/5299